. The significance of serum sST2 and cfDNA in children with severe pneumonia complicated by myocardial damage: serum sST2 and cfDNA in children with severe pneumonia complicated by myocardial damage - Zhao, Tingting (Journal of Medical Biochemistry, 2024)
Objective: The paper aimed to explore the significance of serum sST2 and cfDNA to prevent atrial inflammation in children with severe pneumonia complicated by myocardial damage. Methods: 120 children with severe pneumonia complicated by myocardial damage who were treated in the Children’s Department of the author’s hospital from April 2021 to December 2023 were recruited as research subjects. The children were randomly divided into two groups, one group of 60 children received personalized care intervention based on serum sST2 and cfDNA (personalized care group), and the other group of 60 children received routine care (routine care group). The clinical data of the two groups of patients were compared. The changes in serum sST2 and cfDNA levels of patients were compared before and after care. ELISA kits were used to test atrial inflammation marker levels before and after patient care. The patient’s cardiac function was assessed through cardiac ultrasound. the nursing intervention effects of the two groups was compared. The patient satisfaction with nursing care was compared between the two groups. Results: There was no distinction in the general record of the two groups (P>0.05). Before care, there was no distinction in serum sST2 and cfDNA levels between the two groups (P>0.05). After care, the serum sST2 and cfDNA levels in the personalized care group were lower than those in the routine care group (P<0.05). There was no difference in CRP, cTn, 1L-6 and TNF-α between the two groups before nursing (P>0.05). After nursing, the levels of CRP, cTn, 1L-6 and TNF-α in personalized nursing were lower than those in the conventional nursing group (P<0.05). Parameters such as EF and E/A in the personalized care group were higher than those in the routine care group (P<0.05). The LVEDd and LVESd in the personalized care group were smaller than routine care group (P<0.05). The improvement rate of cardiac function, remission rate of atrial inflammation and 6-month re-hospitalization rate in the personalized care group were lower than conventional care group (P<0.05). The very satisfied rate in the personalized care group was higher than routine care group (P<0.05), and the dissatisfaction rate in the personalized care group was lower than routine care group (P<0.05). Conclusion: Personalized nursing intervention based on serum sST2 and cfDNA can significantly improve the cardiac function of children with severe pneumonia complicated by myocardial damage, reduce the levels of atrial inflammation markers, and advance the satisfaction of children and their families. These findings underscore the importance of applying serum sST2 and cfDNA monitoring in clinical care and the significant benefits of personalized care in preventing atrial inflammation, improving heart health, and improving patient quality of life.